Ethical Considerations for Participatory Health through Social Media: Healthcare Workforce and Policy Maker Perspectives - Rivera-Romero, Octavio; Konstantinidis, Stathis; Denecke, Kerstin; Gabarrón, Elia; Petersen, Carolyn; Househ, Mowafa; Merolli, Mark; Mayer, Miguel Ángel (Yearbook of Medical Informatics, 2020)
Objectives: To identify the different ethical issues that should be considered in participatory health through social media from different stakeholder perspectives (i.e., patients/service users, health professionals, health information technology (If) professionals, and policy makers) in any healthcare context.Methods: We implemented a two-round survey composed of open ended questions in the first round, aggregated into a list of ethical issues rated for importance by participants in the second round, to generate a ranked list of possible ethical issues in participatory health based on healthcare professionals’ and policy makers’ opinions on both their own point of view and their beliefs for other stakeholders’ perspectives.Results: Twenty-six individuals responded in the first round of the survey. Multiple ethical issues were identified for each perspective. Data privacy, data security, and digital literacy were common themes in all perspectives. Thirty-three individuals completed the second round of the survey. Data privacy and data security were ranked among the three most important ethical issues in all perspectives. Quality assurance was the most important issue from the healthcare professionals’ perspective and the second most important issue from the patients’ perspective. Data privacy was the most important consideration for patients/service users. Digital literacy was ranked as the fourth most important issue, except for policy makers’ perspective.Conclusions: Different stakeholders’ opinions fairly agreed that there are common ethical issues that should be considered across the four groups (patients, healthcare professionals, health IT professionals, policy makers) such as data privacy, security, and quality assurance.
Keywords: Social media; ethical issues; clinical ethics; patient-centered care; patient participation